Students’ Perception of Using Quizizz as an Assessment Tool by the Third Year English Department Students of Universitas Riau - Isnaini, Nurul; Eliwarti; Rotua Aruan, Rumiri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
Technology has significantly impacted education, enabling students to access online materials and exercises. One of the online applications used by lecturers in carrying out the learning process is Quizizz. Quizizz is a game-based education platform which has interesting features, so it can increase student motivation in the learning process. This research is to identify students’ perception of using Quizizz as an assessment tool. This study uses a descriptive quantitative research design. The research population was the third year English Department Students of Universitas Riau. The samples were class 6-A and 6-C with the total of 76 students and selected using cluster random sampling technique. The data were collected by using closed-ended questionnaire consists of 7 indicators with the total of 30 questions. The research result was the third year English Department Students have a high perception of the use of Quizizz, because using Quizizz students feel comfortable, satisfied, motivated, practical, better understanding, and feel more confident when doing tasks individually or in groups. However, there are a small number of them who are a little bit challenging and unsatisfactory because they still distracted by notification from other applications when doing exercises through Quizizz.